The Role of Social Media Instagram and Identification of Factors in The Revisit Intention to Gunung Api Purba Nglanggeran - Kumaratih Kumaratungga Dewi; Aditya Solichin; Dhea Ayu Resky Amalia; Tri Wisudawati; Wahyu Adhi Saputro (LPPM Universitas Duta Bangsa Surakarta, 2021)
Tourism is a sector that is currently a priority for the current government. This is not something that is surprising, because Indonesia has thousands of tourist destinations. The types are also very diverse according to the natural, cultural and historical riches in Indonesia which are unique to each. The government is targeting tourism as the largest contributor to foreign exchange. D.I Yogyakarta itself has a tourist attraction that will not disappoint visitors. The designation of Yogyakarta as a tourism area illustrates the potential of this province in a tourism perspective. Various types of tourism objects have been developed in this area, such as nature tourism, historical tourism, cultural tourism, educational tourism, and shopping tourism. One of the tourist sites in D.I Yogyakarta that must be visited is the Nglanggeran Ancient Volcano. This tourist location has received many awards so it is indeed worth a visit. This study aims to determine what factors influence the revisit intentions of tourists to the Gunung Api Purba Nglanggeran. This study uses primary data and secondary data. Primary data is obtained by using direct interviews with tourists who have come to Gunung Api Purba Nglanggeran at least twice. Secondary data is used to strengthen primary data. Secondary data were obtained from relevant sources such as books and journals. This study used a sample of 60 people. The data analysis method used in this study is multiple linear regression analysis. There are three independent variables used in this study, namely attractiveness, service quality and facility, while the dependent variable used in this study is revisit intentions. Based on the results of research using the F-test, it can be concluded that the independent variables of attractiveness, service quality and facility together have an effect on the dependent variable revisit intentions. Based on the results of the research that has been done, it can be seen that there are two variables that affect revisit intentions in Gunug Api Purba Nglanggeran, namely the attractiveness and service quality variables, while there is one variable that has no effect, namely facilities. The attractiveness variable has a t test significance value of 0.0178 while the service quality variable has a t test significance value of 0.0001. The meaning of these two values ​​means that both of them are less than the alpha value of 5% so that both variables are significant. If you look at the value of the regression coefficient on the attractiveness and service quality variables, it is positive so that the increase in the value of both will increase the interest in returning to Gunung Api Purba Nglanggeran